Comparative morphological interpretations on the bones of the pelvic limb of New Zealand rabbit (Oryctolagus cuniculus) and domestic cat (Felis domestica) - El-Ghazali, Hanaa Mohamed; El-behery, Eman Ismail (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Regarding the displaying of the main differences between the pelvic limb of rabbit and cat. Materials and methods: Our work was performed on 10 New Zealand rabbits (Oryctolagus cuniculus) and domestic cats (Felis domestica) with variable ages and of both sexes. After weighing of the animals, sedation, and anesthesia, the animals were examined radiographically. The bones of the pelvic limb were prepared, measured for its length/cm then described and compared. Results: The iliac tuberosity and the conversion of the acetabular notch into foramen were characteristics of Os coxae of the rabbit. The intertrochanteric crest was detected on the femur of the cat. In the rabbit, the leg interosseous space was located in the proximal third of this region while in the cat, it was extended along its length. The first metatarsal was undeveloped in the cat but was absent in the rabbit so metatarsal were four in the rabbit and five in the cat. The digits of the pelvic limbs in both animals were four in number. The distal sesamoid was single, transversely situated, and shuttle-shaped in rabbit but it was absent in cat. Conclusion: So, the chief points of variation between the pelvic limb bones of rabbit and cat enabled us to keep away the commercial fraud and facilitated their use as an animal model for education purposes. http://doi.org/10.5455/javar.2018.e292